2016
DOI: 10.1108/hff-02-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and friction factor in a dimple-pin fin wedge duct with various dimple depth and converging angle

Abstract: Purpose – The dimple is adopted into a pin fin wedge duct which is widely used in modern gas turbine vane cooling structure trailing edge region. The purpose of this paper is to study the effects of dimple depth and duct converging angle on the endwall heat transfer and friction factor in this pin fin wedge duct. Design/methodology/approach – The study is carried out by using the numerical simulations. The diameter of dimples is the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Figure 9 illustrates the heat flux contours on the endwall for the dimples and protrusions with different layouts. A continuous and significant increase of the heat flux value occurs along the streamwise direction which can be related to the flow acceleration effect of the converging duct [21]. The heat flux distributions around the pin fins are obviously higher for the side-by-side arrangement than for the upstream one, and higher for the upstream compared with the downstream arrangement for both dimples and protrusions.…”
Section: Data Reductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 9 illustrates the heat flux contours on the endwall for the dimples and protrusions with different layouts. A continuous and significant increase of the heat flux value occurs along the streamwise direction which can be related to the flow acceleration effect of the converging duct [21]. The heat flux distributions around the pin fins are obviously higher for the side-by-side arrangement than for the upstream one, and higher for the upstream compared with the downstream arrangement for both dimples and protrusions.…”
Section: Data Reductionmentioning
confidence: 95%
“…Rao [20] tested the dimple depth effect on the pressure loss and heat transfer characteristics in a pin fin-dimple channel, where dimples were located between the pin fins and revealed the underlying mechanisms by associating the velocity, and temperature distributions with the pressure loss, and heat transfer together at Reynolds number changing from 8,200 to 50,500. Luo [21] further simulated the dimple depth and converging angle contributions to the heat transfer and friction factor on a dimpled pin-fin wedge duct and concluded that the dimple case with 0.2 relative depth showed the best heat transfer performance at 12.7 converging angle. However, a deeper dimple with larger converging angle provided a better thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, one can find numerous works devoted to the intensification of heat exchange between a solid surface and a liquid flow along it due to the formation of indentations -dimples on the surface [1][2][3][4][5][6][7][8][9][10]. It was established that such surface profiling leads to the generation of non-stationary vortex structures in the flow, mixing of the liquid, and, as a result, noticeable intensification of heat exchange as compared with a smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers [16][17][18][19][20] also have performed experimental and computational studies on the dimple shape, dimple depth, and dimple configuration. Luo et al [21][22][23][24] used numerical methods to study the effects of dimple arrangements, dimple depth, and converging angle on the heat transfer and flow structure in a pin fin channel/duct. The results of the dimple-pin fin channel showed a tremendous heat transfer augmentation performance.…”
Section: Introductionmentioning
confidence: 99%